Polyethylene glycol-400/H3PO2: an eco-friendly reductive system for the synthesis of selanylesters. Issue 11 (29th September 2015) - Perin, G.; Silveira, M. B.; Barcellos, A. M.; Jacob, R. G.; Alves, D.
Abstract : An alternative green method was described for the synthesis of selanylesters by reactions of acyl chlorides with arylselenols, generated in situ by reaction of diaryl diselenides with hypophosphorous acid (H3 PO2 ) using polyethylene glycol-400 (PEG-400) as the solvent. Abstract : An alternative green method was described for the synthesis of selanylesters by reactions of acyl chlorides with arylselenols, generated in situ by reaction of diaryl diselenides with hypophosphorous acid (H3 PO2 ) using polyethylene glycol-400 (PEG-400) as the solvent. These reactions proceeded efficiently at room temperature under N2 using a range of acyl chlorides and diaryl diselenides, both containing electron-withdrawing and electron-donating groups, affording the corresponding selanylesters in moderate to excellent yields. Additionally, PEG-400 can be recovered and directly reused for further reactions.